DIFFERENTIAL ITEM-PERSON FUNCTIONING (DIPF) ON QUIZIZZ-ASSISTED PHYSICS MEASUREMENT QUESTIONS: A RASCH MODEL ANALYSIS - Amiruddin, Mohd Zaidi Bin; Samsudin, Achmad; Suhandi, Andi; Apriliyanti, Nila; Costu, Bayram (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Assessment and measurement have always been crucial topics, especially in physics education, where accurate evaluation is needed to measure students' understanding and mastery of the subject. This study tested the validity and reliability of physics measurement questions administered through the Quizizz platform and identified Differential Item-Person Functioning (DIPF) using the Rasch model-assisted Winstep software. This research design used Item Response Theory (IRT). The study involved 34 high school students from Sidoarjo, East Java, Indonesia. The instrument consisted of 15 multiple-choice questions on basic physics measurements. The results showed that the instrument had good construct validity, with a raw variance explained by the measurement of 22.8%, indicating an effective measure to gauge students' ability. Reliability analysis showed moderate consistency, with a Cronbach Alpha of 70%, although person and item reliabilities were weaker at 63% and 46%, respectively. DIF analysis showed no significant gender bias. Future research should improve the instrument's reliability and consider a broader range of external factors to understand student performance comprehensively.